2021
DOI: 10.1109/access.2021.3096729
|View full text |Cite
|
Sign up to set email alerts
|

Volume Conduction for Powering Deeply Implanted Networks of Wireless Injectable Medical Devices: A Numerical Parametric Analysis

Abstract: The use of networks of wireless active implantable medical devices (AIMDs) could revolutionize the way that numerous severe illnesses are treated. However, the development of sub-mm AIMDs is hindered by the bulkiness and the transmission range that consolidated wireless power transfer (WPT) methods exhibit. The aim of this work is to numerically study and illustrate the potential of an innovative WPT technique based on volume conduction at high frequencies for powering AIMDs. In this technique, high frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In the in vitro study, the external system was set to apply HF bursts with an amplitude of 39 V, which should produce an electric field in the middle of the region located between the two external textile electrodes with an amplitude of about 325 V/m [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the in vitro study, the external system was set to apply HF bursts with an amplitude of 39 V, which should produce an electric field in the middle of the region located between the two external textile electrodes with an amplitude of about 325 V/m [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…This ideal scenario did not include different conductivity layers as those that could be present due to other tissues. However, we have in silico demonstrated using a multilayered geometry, that the electric field generated by the HF current bursts delivered by the external system are coarsely uniform in the region located between the external electrodes [ 30 ]. More importantly, we recently demonstrated in arms and lower legs of healthy humans that electric powers above 2 mW and 5 mW respectively could be obtained using needle electrodes (diameter: 0.4 mm, length: 3 mm) implanted approximately 1.75 cm deep [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SAR indicates the heat dissipated per unit of tissue mass and is calculated averaging over 10 g of mass and 6 minutes. Previous studies have demonstrated, numerically [54] and in humans [30], that it is possible to transfer powers in the order of milliwatts to implanted devices via volume conduction of HF current bursts that comply with these safety standards.…”
Section: Discussionmentioning
confidence: 99%
“…This ideal scenario did not include different conductivity layers as those that could be present due to other tissues. However, we have in silico demonstrated using a multilayered geometry, that the electric field generated by the HF current bursts delivered by the external system are coarsely uniform in the region located between the external electrodes [30]. More importantly, we recently demonstrated in arms and lower legs of healthy humans that electric powers above 2 mW and 5 mW respectively could be obtained using needle electrodes (diameter: 0.4 mm, length: 3 mm) implanted approximately 1.75 cm deep [31].…”
Section: Discussionmentioning
confidence: 99%
“…A portion of the HF current picked up by the devices is not directly rectified to perform stimulation but used to power the electronics of the implant (e.g., for control and communications) and, in this sense, it can be understood that the implants employ WPT based on volume conduction. In fact, in a series of recent works, we have advocated for, and studied, the use of volume conducted HF current bursts applied through textile electrodes to power elongated implants in general, not only stimulators [29][30][31]. Remarkably, according to the approach we propose, the implants can be conceived as thin, flexible and elongated devices suitable for implantation by means of injection [27].…”
Section: Introductionmentioning
confidence: 99%